Transportation System Efficiency Evaluation through the Main Logistics Activities Process: A Case Study of ABC Company - Tumchaiyangkul, Nontakon; Rodjanapradied, Rahuth; Cheewinsiriwat, Pannee (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The objectives of this research were: 1) to create indicators to assess the efficiency of transport systems through the main logistics activities process, and 2) to evaluate the efficiency of the transport systems using the indicators on the main logistics activities, a case study of ABC transport company. The researcher reviewed the related literature on the main logistics activities for transport and accuracy principles and then developed the indicators before taking to the in-depth interview. The assessment forms of indicators were delivered to a sample consisting of 10 participants who were related to the company’s transport activities in order to examine the accuracy of the developed indicators. After that, the completed efficiency assessment forms were used to evaluate the efficiency of the company’s transport system (a case study). The research results show that the appropriate indicators in evaluating the efficiency of the transport system included the three main activities: communication, unloading and packing, and transporting. Each activity consisted of 5 dimensions (15 indicators): 1) accuracy, 2) quality, 3) place, 4) time, and 5) cost. The overall evaluation of the efficiency of ABC company’s transport system averaged 4.72. Although the company’s overall evaluation was at an excellent level, the average duration indicator in sending orders within the organization was little at 2.00. Therefore, the company should put more emphasis on developing a system for sending orders in the organization to be faster in order to reduce the impact and prevent problems that might occur by using communication technology: a database system or mailing system within the organization.